Relaxor Behavior in Ordered Lead Magnesium Niobate (PbMg1/3Nb2/3O3) Thin Films. (30th November 2018) - Shetty, Smitha; Damodaran, Anoop; Wang, Ke; Yuan, Yakun; Gopalan, Venkat; Martin, Lane; Trolier‐McKinstry, Susan
Abstract: The local compositional heterogeneity associated with the short‐range ordering of Mg and Nb in PbMg1/3 Nb2/3 O3 (PMN) is correlated with its characteristic relaxor ferroelectric behavior. Fully ordered PMN is not prepared as a bulk material. This work examines the relaxor behavior in PMN thin films grown at temperatures below 1073 K by artificially reducing the degree of disorder via synthesis of heterostructures with alternate layers of Pb(Mg2/3 Nb1/3 )O3 and PbNbO3, as suggested by the random‐site model. 100 nm thick, phase‐pure films are grown epitaxially on (111) SrTiO3 substrates using alternate target timed pulsed‐laser deposition of Pb(Mg2/3 Nb1/3 )O3 and PbNbO3 targets with 20% excess Pb. Selected area electron diffraction confirms the emergence of (1/2, 1/2, 1/2) superlattice spots with randomly distributed ordered domains as large as ≈150 nm. These heterostructures exhibit a dielectric constant of 800, loss tangents of ≈0.03 and 2× remanent polarization of ≈11 µC cm −2 at room temperature. Polarization–electric field hysteresis loops, Rayleigh data, and optical second‐harmonic generation measurements are consistent with the development of ferroelectric domains below 140 K. Temperature‐dependent permittivity measurements demonstrate reduced frequency dispersion compared to short range ordered PMN films. This work suggests a continuum between normal and relaxor ferroelectric behavior in the engineered PMN thin films. Abstract : This work reports the first PMN (PbMg1/3 Nb2/3 O3 ) thin film with long‐range cation order via synthesis of heterostructures with alternate layers of Pb(Mg2/3 Nb1/3 )O3 and PbNbO3, as suggested by the random‐site model. The comparative study elucidates the impact of increased cation order in PMN on its characteristic relaxor ferroelectric behavior.